Effect Mechanism of Penstock on Stability and Regulation Quality of Turbine Regulating System. (19th November 2014) - Guo, Wencheng; Yang, Jiandong; Chen, Jieping; Teng, Yi
Abstract : This paper studies the effect mechanism of water inertia and head loss of penstock on stability and regulation quality of turbine regulating system with surge tank or not and proposes the construction method of equivalent model of regulating system. Firstly, the complete linear mathematical model of regulating system is established. Then, the free oscillation equation and time response of the frequency that describe stability and regulation quality, respectively, are obtained. Finally, the effects of penstock are analysed by using stability region and response curves. The results indicate that the stability and regulation quality of system without surge tank are determined by time response of frequency which only depends on water hammer wave in penstock, while, for system with surge tank, the time response of frequency depending on water hammer wave in penstock and water-level fluctuation in surge tank jointly determines the stability and regulation quality. Water inertia of penstock mainly affects the stability and time response of frequency of system without surge tank as well as the stability and head wave of time response of frequency with surge tank. Head loss of penstock mainly affects the stability and tail wave of time response of frequency with surge tank.